The Role of Criminal Investigator in Disabilities Persecution - Ali Mashuri (Law Development Journal, 2020)
The aim of this study is to know the procedures for the role of investigators in investigating criminal acts of persecution of victims of disabilities. Role of Investigators in Investigating Criminal Acts of Persecution of Victims. Factors obstructing the role of Investigators in investigating criminal acts of abuse of victims of disabilities at the Police. This study uses an approach method juridical empirical. The conclusion of this study is Procedure for investigating criminal acts of mistreatment of victims of disabilities at Tambakromo Police. The law enforcement process begins based on the report: LP/B/392020/Jateng/Res.Pt/Sek.Tbr. Making Reports, Visiting the Crime Scene, Recording witnesses, Report to the leadership, conduct an investigation. The role of investigators in investigating criminal acts of persecution of victims of disabilities at Tambakromo Police. Based on the Police Report Number: LP/B/392020/Jateng/Res.Pt/Sek.Tbr. January 13, 2020; Investigation warrant Number: SP. Sidik/01.A/I/2020/Reskrim, dated January 13, 2020; Letter of notification of commencement of investigation Number: SPDP/01/I/Res. 1.6/2020/Reskrim, 17 January 2020; then Crime Scene Arrest, Detention, Confiscation, Statement of witnesses, statement of the suspect Visum Et Repertum, Evidence. factors inhibiting the role of the investigator in investigating the criminal act of assaulting victims of disabilities at the Tambakromo Police, Whereas the report of the incident of the case with the case that is reported is a long difference so that the investigator in the process of conducting the examination of the witness is constrained in the witness summoning, because the witness cannot be present at the appointed time. Lack of human resources for investigators, lack of infrastructure in the investigation, and how to deal with it Coordinating with victims so that witnesses who are presented when summoned can be present at the office according to the time specified, Supervise and inspect every activity and administrative worksheets made by assistant investigators, Lack of budget submitted for the following year, but rarely realized.